One-Pot Synthesis of [1,2,3]Triazolo[1,5-a]quinoxalin-4(5H)-ones by a Metal-Free Sequential Ugi-4CR/Alkyne–Azide Cycloaddition Reaction - Yan, Yan-Mei; Li, Hao-Yang; Zhang, Min; Wang, Rong-Xin; Zhou, Chen-Guang; Ren, Zhen-Xing; Ding, Ming-Wu (Synlett, 2020)
A convenient and one-pot approach to prepare [1,2,3]triazolo[1,5-a]quinoxalin-4(5H)-ones by a metal-free sequential Ugi-4CR/alkyne–azide cycloaddition reaction has been developed. The reaction of 2-azidobenzenamines, aldehydes, propiolic acids, and isocyanides produced the Ugi adducts, which were transformed to the [1,2,3]triazolo[1,5-a]quinoxalin-4(5H)-ones in moderate to good yields via alkyne–azide cycloaddition reaction.
Keywords: one-pot; metal-free; [1,2,3]triazolo[1,5-a]quinoxalin-4(5H)-one; Ugi reaction; alkyne–azide cycloaddition reaction